EKSISTENSI NEGARA PANCASILA DALAM PARADIGMA USHUL FIKIH PROGRESIF - Moh. Dahlan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2013)
Indonesia is not a religious country, but the country that acknowledged Pancasila pluralism in ail its aspects. Therefore, the criticism of radical Islamic groups in Indonesia does not have the constitutional and legal basis for religion. Even the constitution and policies against religious law, namely the achievement of public norms. From the foregoing principal problem to be solved is how to formulate a progressive ushul fiqh paradigm that can accommodate and support the existence of the state ideology Pancasila as final and binding. To answer this problem, the authors use norms approach, whereas the method used is the method of interpretation of Hans G Gadamer productive. Results show that the ushul fiqh paradigm discussion be developed is the paradigm fik ih ushul progressive interpretation based ow productive to dig Maqasid al-Shari'ah and legal principles fiqh to uphold the legality of the existence of the state ideology of Pancasila as final and binding.